Impacts of the hydrological potential change on the energy matrix of the Brazilian State of Minas Gerais: A case study. (August 2019) - Melo, Leonardo B.; Estanislau, Fidéllis B.G.L.e; Costa, Antonella L.; Fortini, Ângela
Abstract: The vulnerability of electric potential generation from water resources has been evidenced due to uncertainties of climatic origin and energy planning. Changes in rainfall regimes are multifactorial phenomena difficult to model. Rainfall is the main natural way of restoring the reservoir levels of hydroelectric power plants. The reduction in rainfall levels may increase in the coming years, resulting in a probable change of the energy matrix configuration of the state of Minas Gerais (MG). This could reduce the share of renewable sources increasing dependence on the importance of energy from fossil fuels, which are the immediate primary sources of energy available. Prior examinations have portrayed the depletion of hydroelectricity in Brazil, or its macro-regions, however this work tries to supply a more focused look at the effects on the electricity and social sectors of the state of Minas Gerais. The study developed in this paper aims to investigate the hydrological potential alteration impacts and consequences on the energy matrix of the state, the greenhouse gas emissions and the social reflexes of these changes due to scenarios motivated by climate change. The investigation intends to show the importance of the water-energy-emissions nexus for energy planning and decision-making, in order to evaluate the best options for dealing with adverse and potentially destabilizing conditions. The results of the analyses show that while hydropower demand was 5.24 Mtoe in 2015, in 2030 the supply of hydropower will be 5.81 Mtoe and 4.72 Mtoe, for the conservative and severe scenarios, respectively. In addition, the effect of climate change may require an increase in the share of non-renewable sources in the energy matrix, which could increase CO2 e emissions from 4.2% to 7.4% by 2030, compared to the levels in 2016. Highlights: Reduction in rainfall levels will change the energy matrix configuration of MG state. Population growth will boost demand for energy. It is shown the importance of the water-energy-emissions nexus for energy planning and decision-making. The energy matrix may considerably increase the CO2 e emissions by 2030, compared with 2016 levels in the MG state.